2012
DOI: 10.1080/13691058.2011.628411
|View full text |Cite
|
Sign up to set email alerts
|

Occupational stigma as a primary barrier to health care for street-based sex workers in Canada

Abstract: Individuals working in the sex industry continue to experience many negative health outcomes. As such, disentangling the factors shaping poor health access remains a critical public health priority. Within a quasi-criminalised prostitution environment, this study aimed to evaluate the prevalence of occupational stigma associated with sex work and its relationship to barriers to accessing health services. Analyses draw on baseline questionnaire data from a community-based cohort of women in street-based sex wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
192
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 239 publications
(205 citation statements)
references
References 34 publications
6
192
1
6
Order By: Relevance
“…Health providers sometimes express greater bias against sex-workers than other people LWH (Roche & Keith, 2014;Rogers et al, 2014). A study in Canada, for example, found sex-work stigma to be an independent determinant of restricted access to health care (Lazarus et al, 2012). The persistence of stigma against FSW even in contexts where legal barriers have been removed suggests that targeted services will continue to play an important role in meeting sex-workers' health needs.…”
Section: Discussionmentioning
confidence: 99%
“…Health providers sometimes express greater bias against sex-workers than other people LWH (Roche & Keith, 2014;Rogers et al, 2014). A study in Canada, for example, found sex-work stigma to be an independent determinant of restricted access to health care (Lazarus et al, 2012). The persistence of stigma against FSW even in contexts where legal barriers have been removed suggests that targeted services will continue to play an important role in meeting sex-workers' health needs.…”
Section: Discussionmentioning
confidence: 99%
“…O estigma associado ao trabalho sexual tem sido apontado como uma barreira de acesso aos serviços (Lazarus et al, 2012), pelo que os pressupostos da não discriminação e do não julgamento são essenciais para pessoas estigmatizadas que raramente se sentem confiantes para procurar ajuda nos serviços de saúde e sociais formais. No campo da educação em saúde, as organizações adotam uma abordagem educativa (Ewles;Simnett, 2003;Feio;Oliveira, 2015), na prestação de informação genérica sobre saúde sexual e reprodutiva; sobre o uso correto e consistente do preservativo, bem como sobre os diferentes preservativos, incluindo o feminino; sobre cuidados de higiene; sensibilizam para a importância da realização do Plano Nacional de Vacinação (PNV) e rastreios a DST; prestam aconselhamento e esclarecem dúvidas.…”
Section: Tem a Ver Também Com A Nossa Pedagogia é Importante Ensinarunclassified
“…Nessa sequência, enfatizam aspectos re-lacionados com a saúde física e mental, bem como questões associadas à segurança, nomeadamente burnout, estresse pós-traumático, estresse, depressão, dependência de álcool e drogas, alergia ao látex, morte, ferimentos/lesões a nível muscular e do esqueleto; coação para relações desprotegidas e gravidez; violência e assédio perpetrados por clientes e/ou proxenetas. Para diversos autores (Lazarus et al, 2012;Oliveira, 2011;Ross et al, 2012), esses e outros riscos encontram-se associados à legislação vigente e à estigmatização das(os) TS.…”
Section: Introductionunclassified
“…The international body of evidence concerning harms associated with sex work in a criminalized context is increasingly unambiguous. As Kate Shannon, Chris Bruckert, and Frances Shaver state, a "large body of scientific evidence from Canada, Sweden and Norway (where clients and third parties are criminalized), and globally clearly demonstrates that criminal laws targeting the sex industry have overwhelmingly negative social, health, and human rights consequences to sex workers, including increased violence and abuse, stigma, HIV and inability to access critical social, health and legal protections" (Shannon et al 2014;see Chu & Glass 2013;Csete & Cohen 2010;Dodillet & Östergren 2011;Lazarus et al 2012;Lowman 2000;Lowman 2004;Shannon 2010;Shannon & Csete 2010;Shannon et al 2008;Skarhed 2010;Skilbrei & Holmström 2013; This policy area is complicated in any jurisdiction, and Canada is no exception. The terrain is demarcated by a federal legal framework in which the buying and selling of sex among consenting adults is legal.…”
Section: Introductionmentioning
confidence: 99%